Mechanisms of state-private partnership as the basis of development of consultative and diagnostic care - Kravchenko, V. V. (Journal of Education, Health and Sport, 2017)
The aim of the study is to substantiate the expediency of translating the Consultative and Diagnostic Centers (CDCs) into the principles of public-private partnership (PPP).Materials and methods. To achieve this aim, general scientific methods of analysis, synthesis, generalization, interpretation of scientific data, as well as systematic approach, dialectical principles of comparison were used in the work.ResultsThe article analyzes social aspects and reserves for the development of consultative and diagnostic care in the public health sector.It is determined that one of the significant organizational and technological reserves for increasing the availability, timeliness and efficiency of providing consultative and diagnostic care and optimizing the work of the CDCs is the modernization on the basis of PPP. The functional and organizational structure of the CDC model on the principles of PPP is presented.Conclusions. In the difficult economic conditions of the country, the modernization of the CDCs using the mechanisms of PPP is the basis of organizational and technological reserves to improve accessibility, efficiency of consultative and diagnostic care and introducing anti-crisis management in the CDCs.